Ga1-xAlxAs nanostructures grown on the GaAs Surface by Ion Implantation - Sodikjanov J.Sh. (Zien Journals, 2023)
The surface structure and electronic characteristics of nanocrystalline phases and 2-7-nm-thick Ga1-xAlxAs films formed on the GaAs(111) surface by Al+ ion implantation are investigated. The bandgap Eg of the Ga0.5Al0.5As nanocrystalline surface phase 25-30 nm in size is determined to be 2.8-2.9 eV
Keywords: morphology; ion implantation; electronic structure